1992
DOI: 10.1017/s0043174500056964
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Restriction Fragment Length Polymorphisms in Chloroplast DNA of Five Leafy Spurge (Euphorbiaspp.) Accessions

Abstract: Chloroplast DNA (cpDNA) restriction fragment length polymorphisms (RFLPs) were analyzed to assess genetic variation and relatedness among selections of North American and Eurasian leafy spurge. Leafy spurge accessions from Nebraska, Montana, Russia, Italy, and Austria were evaluated. Total DNA was extracted from young leaves and digested with the restriction endonuclease,EcoRI. CpDNA fragment patterns were determined by Southern blot analysis using mung bean cpDNA probes. Colinearity between the mung bean and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…Marker-based analyses of jointed goatgrass (Aegilops cylindrica) and the aquatic weed Egeria densa showed low levels of genetic diversity and little structuring in both native and introduced populations on different continents (Carter and Sytsma 2001;Pester et al 2003). In contrast, high levels of marker-based diversity and genetic structuring have been reported in both native European and invading North American populations of garlic mustard (Alliaria petiolata) and leafy spurge (Nissen et al 1992;Rowe et al 1997;Meekins et al 2001). Yet another structuring pattern has been detected using AFLP markers in Rubus alceifolius: this species has high levels of diversity in its native southeast Asian range, reduced diversity among introduced populations in Madagascar, and virtually no diversity in invasive populations on other Indian Ocean islands (Amsellem et al 2000).…”
Section: Continental and Global Scalementioning
confidence: 99%
“…Marker-based analyses of jointed goatgrass (Aegilops cylindrica) and the aquatic weed Egeria densa showed low levels of genetic diversity and little structuring in both native and introduced populations on different continents (Carter and Sytsma 2001;Pester et al 2003). In contrast, high levels of marker-based diversity and genetic structuring have been reported in both native European and invading North American populations of garlic mustard (Alliaria petiolata) and leafy spurge (Nissen et al 1992;Rowe et al 1997;Meekins et al 2001). Yet another structuring pattern has been detected using AFLP markers in Rubus alceifolius: this species has high levels of diversity in its native southeast Asian range, reduced diversity among introduced populations in Madagascar, and virtually no diversity in invasive populations on other Indian Ocean islands (Amsellem et al 2000).…”
Section: Continental and Global Scalementioning
confidence: 99%
“…An initial survey with eleven restriction enzymes (BamHI, BclI, CfoI, C/la, EcoRI, EcoRV, HindIII, HpaII, KpnI, XbaI, XhoI7) and individual leafy spurge accessions was conducted to determine which restriction enzymes would reveal the largest differences in cpDNA. DNA from Nebraska, Montana, Austria, Italy, and Russia leafy spurge plants was digested with EcoRI (Nissen et al 1992), and DNA of individuals from Nebraska, Montana, Austria, Turkey, Hungary, Yugoslavia, and Russia was digested with the other 10 enzymes. Enzymes revealing most polymorphisms among accessions using the 14 cpDNA probes were EcoRI, EcoRV, and HindIII.…”
Section: Restriction Enzyme/probe Surveymentioning
confidence: 99%
“…Heterologous probes detected leafy spurge cpDNA polymorphisms throughout the chloroplast genome, which has been estimated at 120,000 to 150,000 base pairs in leafy spurge (Nissen et al 1992). Digested DNAs from representatives of each population were run on a common gel so polymorphisms could be directly compared (Figure 1).…”
Section: Cpdna Polymorphismsmentioning
confidence: 99%
“…Six mung bean (Phaseolus aureus L.) cpDNA PstI and SalI restriction fragments, cloned into the plasmid vector pBR322, were used as hybridization probes in this study (15,16). Previous research has shown that mung bean cpDNA probes hybridize well to membrane bound leafy spurge cpDNA (13). Mung bean cpDNA probes were labelled with digoxigenin-11-2'-deoxyuridine-5'-triphosphate by random priming (6).…”
Section: Genotype Characterizationmentioning
confidence: 99%
“…Attempts have been made to determine genetic variation in some weed species targeted for biological weed control in North America (13,14). The genetic diversity and population structure of exotic North American genotypes compared to native Eurasian populations probably are characterized better in leafy spurge than any other weed.…”
Section: Introductionmentioning
confidence: 99%